209 - MANUAL LYMPHATIC DRAINAGE IN THE TREATMENT OF WOMEN WITH CHRONIC VENOUS INSUFFICIENCY AND EDEMA OF THE LOWER LIMBS (Fiep Bulletin - online, 2011)
Chronic venous insufficiency is a disease that affects the venous system and is caused by a valvular incompetence, often leading to secondary edema. The objective of this study was to evaluate the effects of manual lymphatic drainage on perimetry, goniometry and quality of life, in women with chronic venous insufficiency and edema of the lower limbs. The sample consisted of four women aged between 50 and 75 years. Ten manual lymphatic drainage sessions were carried out. The data were analyzed by descriptive statistics and the two-tailed student's "t" test, applying a level of significance of p?0.05. The results obtained were as follows: A reduction in all the points of perimetry in the right leg, with a mean difference between pre- and post-treatment of -0.88 ± 0.46 cm (p=0.00043) and for the left leg, -0.43 ± 0.76 cm (p=0.128). An increase in range of movement was obtained, with a mean difference pre- and post-treatment for the right leg of 4.25 ± 4.00 degrees (p=0.081), and for the left leg, 5.20 ± 5.38 degrees (p=0.10). In terms of quality of life, an increase was observed in all eight domains, resulting in a p=0.0022, with the greatest gains being in relation to the domains of physical and emotional limitation (50 points), followed by the domains of social aspects (31.25 points), pain (25.25 points), mental health (25 points), vitality (15 points), general state of health (10.5 points) and functional capacity (8.75 points). We conclude that manual lymphatic drainage contributes to reducing edema, increasing range of movement, and improving quality of life among women with chronic venous insufficiency and edema of the lower limbs.
Keywords: Chronic Venous Insufficiency; Physiotherapy; Manual Lymphatic Drainage